RESTRICTIONS ON THE ACQUISITION OF CERTAIN CATEGORIES OF REAL ESTATE IN RELATION TO THE BASIC MARKET FREEDOMS IN THE EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2020)
The acquisition of ownership of real estate in the European Union is regulated by national laws of the Member States. As one of the cornerstones of the EU legal system is the prohibition of discrimination based on the nationality, all national systems have to allow citizens of other EU Member States to acquire the ownership of real estate under the same conditions that apply to their own citizens. Nevertheless, there are certain exceptions to this rule that allow the Member States to exclude certain categories of real estate from being accessible to non-citizens, such as agricultural land, forests, secondary homes and excluded areas under special nature protection regimes. Moreover, many States have been granted the right to transitional restrictions for the acquisition of agricultural land upon their accession to the EU, lasting for several years, during which period non-citizens were prevented from acquiring the ownership of such property. After those grace periods have ended, many countries have introduced different new measures aiming at protecting their agricultural land from being taken over by foreign investors, only by different means. Such measures, even though they are not explicitly preventing non-citizens from the acquisition of the ownership, make it practically almost impossible for them to get it. Although the objectives behind all these practices of the Member States, such as prevention of the land-grabbing and land speculation, preserving agricultural communities and supporting the development of rural regions are quite justifiable, they still collide with basic market freedoms in the European Union. The paper will show the multitude of legal approaches to the acquisition of real estate by non-citizens throughout the European Union. It will show the development of national policies regarding the “restricted” categories of real estate – agricultural land, forest land and land under specific protection regimes – and these national legal norms will be put in perspective with the basic freedoms of the EU internal market. The aim of the paper will be to question the validity and legality of such restrictions that are still in different covert forms very present on the territory of the EU Member States and offer an answer to whether such a practice presents an infringement of the internal market of the European Union.